Analisis Sumber Informasi Budaya Suku Rejang dalam Menciptakan Layanan Rejang Corner Perpustakaan Institut Agama Islam Negeri Curup - Iswanto, Rahmat; Rodin, Rhoni; Jurianto, Jurianto (IAIN Curup, 2019)
The purpose of this study was to analyze cultural information sources of the rejang tribe in creating a Rejang corner service at the IAIN Curup Library. This research is descriptive qualitative. Data collection used interview, observation and documentation methods. The results of the study showed that there are two sources of information about the rejang tribe, the first, information sources based on library materials, including printed and non-printed works. Printed works consist of books, serials, activity reports, etc., while non-printed works are recorded media in the form of audio-visual media. The second, information sources based on cultural elements include art, technological systems and equipment, community organization systems, languages, livelihood systems and economic systems, knowledge systems, and religious systems. Rejang corner service occupies one of the rooms on the 1st floor of the IAIN Curup Library. The rejang corner service was formed because there were several collections relating to the culture of the tribe in the form of printed and non-printed works.